Pengaruh Penggunaan MetodeWahdah Terhadap Kemampuan Menghafal Surah Al-Fiil dan Al-Lahab Pada Anak Berkebutuhan Khusus (Tunagrahita Ringan) di SLB B C YGP Cibatu - Maria, Anly; Nursalafiah, Iis Isnaeni (STAI Al-Musaddadiyah Garut, 2022)
Memorization is a crucial ability required during the learning process, especially when children are engaged in their educational journey. Memorization in the context of learning, particularly memorizing the Quran, involves the efforts to educate, guide, and maintain Quranic memorization. Therefore, children with special needs, specifically those with intellectual disabilities, require specialized instruction for Quranic memorization as the Quran is a guide for all humanity. This study aims to describe: (1) the memorization ability of special needs students in class IX at SLB BC YGP Cibatu in memorizing the Surahs Al-Fiil and Al-Lahab before any intervention, (2) the application of the Wahdah Method for special needs students at SLB BC YGP Cibatu in memorizing the Surahs Al-Fiil and Al-Lahab before any intervention, and (3) the impact of using the Wahdah Method on the memorization abilities of special needs students in class IX at SLB BC YGP Cibatu for the Surahs Al-Fiil and Al-Lahab after the intervention. The sample in this study consists of students with mild intellectual disabilities at SLB BC YGP Cibatu. This research employs the Single Subject Experiment method. Data collection techniques include tests, observations, interviews, and documentation. The results of this study indicate that teaching using the Wahdah Method is highly effective in enhancing the memorization abilities of the children, as evidenced by the improvement in scores across all subjects. The data analysis shows that the post-test scores for the first subject in Surah Al-Fiil and Al-Lahab are 92. For the second subject, the score for Surah Al-Lahab is 88, and for Surah Al-Fiil, it is 80. Statistical analysis reveals that the calculated t-value for Surah Al-Lahab is significantly higher than the critical t-value, with 12.04 > 1.000. Similarly, for Surah Al-Fiil, the t-value is 2.37 > 1.000. Based on these results, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that there is a significant impact on the memorization abilities of special needs children using the Wahdah Method at SLB BC YGP Cibatu. Keywords: mild intellectual disability, Wahdah Method